A Rendezvous with the Ghosh Brothers: a sneak peek into Bengal's homegrown exploitation cinema. Issue 4 (2nd October 2019) - Chatterjee, Subhajit
ABSTRACT: The article is part of a broader research project that considers the low budget sector of contemporary Bengali cinema and its relationship to the regional popular culture. I intend to draw critical attention towards a recent and unique development in Bengali popular cinema that stages a bizarre encounter between high art and low-brow sensibilities in the regional culture. This previously uncharted terrain also testifies to Bengali cinema's new found kinship with certain established practices of exploitation cinema prevalent in the West as well as many Asian countries, which complicate conventional generic classifications, as well as prevalent taste cultures. The article uses the author's in-depth interview with the Ghosh Brothers, a significant directorial duo working in this field, to chart the economic and cultural networks that sustain such a fringe phenomenon. The larger aim of the project is to unravel the socio-political contexts overseeing such precarious developments in a regional popular culture and to understand their relevance in the context of widely expanding studies of marginal cinematic cultures